Western civilizations : - Cole, Joshua (W.W. Norton & Company, 2014)
The engaging narrative and carefully crafted, innovative pedagogical tools in Western Civilizations are based on the co-authors’ own teaching experiences. The text provides balanced coverage, places the West in a larger global context, and carefully integrates new research. In the eighteenth edition, the early modern period has been completely overhauled―and now includes a new chapter on the Atlantic World.